Polyglycolic acid copolymer and preparation method thereof

Through the esterification reaction, prepolymerization and polycondensation process, a specific catalyst system and process flow is used to prepare polyglycolic acid copolymers with high thermal stability and high viscosity, which solves the problem of easy oxidation and degradation of polyglycolic acid and improves its processing performance.

CN119143976AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310704027.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The melting point of the existing polyglycolic acid is close to the thermal decomposition temperature, which is easy to oxidize and degrade during the preparation process, and the processing window is narrow, resulting in unstable performance and difficult processing.

Method used

Using a specific catalyst system and process flow, the reaction temperature and pressure are adjusted through the esterification reaction, prepolymerization and polycondensation process to prepare polyglycolic acid copolymers with high thermal stability and high viscosity.

Benefits of technology

The thermal stability, viscosity and mechanical properties of polyglycolic acid copolymers are improved, the oxidation and degradation problems are solved, and the processing window is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of polyglycolic acid reaction, and discloses a polyglycolic acid copolymer and a preparation method thereof.The method comprises the steps that at the first temperature, a first monomer, a second monomer and a third monomer are subjected to an esterification reaction under the action of a first catalyst and a second catalyst, and a precursor is obtained; heating to a second temperature, and carrying out prepolymerization reaction on the precursor under a first pressure to obtain an intermediate; reducing the pressure to second pressure, and performing condensation polymerization on the intermediate to obtain a copolymer; the first monomer is glycollic acid and / or glycollic acid ester; the second monomer is selected from binary acid and / or binary anhydride; the third monomer is selected from dihydric alcohol; the second catalyst is a RE (R1) 3 type catalyst. The method is low in cost and easy to process, the polymer is stable and not easy to oxidize and degrade in the processing process, and the prepared polyglycolic acid copolymer is high in thermal stability, high in viscosity and excellent in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polyglycolic acid, in particular to a polyglycolic acid copolymer and a preparation method thereof. Background Art

[0002] With the development of the economy and society, society has increasingly higher environmental requirements for polymer materials. The development of degradable polymer materials is an effective way to solve the problem of "white pollution".

[0003] At present, degradable polymer materials also have certain limitations. For example, the simplest linear aliphatic polyester polyglycolic acid (PGA), although it has high strength, modulus and gas barrier properties, has a melting point (220-225°C) close to the thermal decomposition temperature (about 250°C), poor thermal stability, difficult synthesis and processing, narrow processing window, and serious degradation of product performance during processing. In addition, PGA has too high rigidity (the elongation at break is generally between 30-40%), making it unsuitable for direct use as a membrane material. It is insoluble in common organic solvents and has great limitations in processing methods and applications. In addition, the raw material glycolic acid has insufficient thermal stability and is very prone to thermal oxidative degradation under condensation reaction conditions.

[0004] At present, the main method of copolymerization of PGA is ring-opening polymerization, and the main monomers copolymerized with it are lactide, ε-caprolactone, trimethylene carbonate, etc. The advantages of ring-opening copolymerization are low catalyst usage, excellent product thermal properties, and high copolymer molecular weight, but it also has the disadvantages of high raw material cost and small variety, which greatly limits its application. The high molecular weight copolymer obtained by polycondensation between glycolic acid or ethanol ester and other polyester monomers can greatly reduce the cost of raw materials, and does not require long-term solid phase polycondensation, which is conducive to large-scale production and preparation. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of the prior art that the melting point of polyglycolic acid is close to the thermal decomposition temperature, it is easy to oxidize and degrade during the preparation process, and the processing window is narrow. A polyglycolic acid copolymer and a preparation method thereof are provided. The method has lower cost than ring-opening polymerization, and adopts a suitable catalyst system and pressure system to synergistically ensure that the product performance is stable during the processing, it is not easy to oxidize and degrade, it is easy to process, and a polyglycolic acid copolymer with high thermal stability, high viscosity and excellent mechanical properties can be obtained.

[0006] In order to achieve the above object, the present invention provides a first aspect of a method for preparing a polyglycolic acid copolymer, which comprises the following steps:

[0007] (1) subjecting a first monomer, a second monomer, and a third monomer to an esterification reaction under the action of a first catalyst and a second catalyst at a first temperature to obtain a precursor;

[0008] (2) heating the precursor to a second temperature and the first pressure to obtain an intermediate by subjecting the precursor to a prepolymerization reaction; reducing the pressure to a second pressure and subjecting the intermediate to a condensation polymerization reaction to obtain a copolymer;

[0009] The first monomer is glycolic acid and / or glycolic acid ester;

[0010] The second monomer is selected from dibasic acids and / or dibasic acid anhydrides;

[0011] The third monomer is selected from diols;

[0012] The second catalyst is RE (R 1 ) 3 Type catalyst, RE is a rare earth metal element, R 1 is selected from halogen, alkoxy, aryloxy, acetylacetonate and R 2 At least one of the COO- groups, R 2 C 1 -C 30 of alkyl.

[0013] The second aspect of the present invention provides a polyglycolic acid copolymer prepared by the above method.

[0014] Through the above technical solution, the present invention has the following beneficial effects:

[0015] (1) The preparation method of the present invention includes esterification reaction, prepolymerization and polycondensation process. The specific catalyst system and the specific process flow work together to solve the problem of easy oxidation and degradation and difficult processing in the preparation process of polyglycolic acid.

[0016] (2) The polyglycolic acid copolymer prepared by the specific method of the present invention has excellent mechanical properties such as high thermal stability, high viscosity and high toughness. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The first aspect of the present invention provides a method for preparing a polyglycolic acid copolymer, which comprises the following steps:

[0019] (1) subjecting a first monomer, a second monomer, and a third monomer to an esterification reaction under the action of a first catalyst and a second catalyst at a first temperature to obtain a precursor;

[0020] (2) heating the precursor to a second temperature and the first pressure to obtain an intermediate by subjecting the precursor to a prepolymerization reaction; reducing the pressure to a second pressure and subjecting the intermediate to a condensation polymerization reaction to obtain a copolymer;

[0021] The first monomer is glycolic acid and / or glycolic acid ester;

[0022] The second monomer is selected from dibasic acids and / or dibasic acid anhydrides;

[0023] The third monomer is selected from diols;

[0024] The second catalyst is RE (R 1 ) 3 Type catalyst, RE is a rare earth metal element, R 1 is selected from halogen, alkoxy, aryloxy, acetylacetonate and R 2 At least one of the COO- groups, R 2 C 1 -C 30 of alkyl.

[0025] In the present invention, a specific preparation method enables the polyglycolic acid to have high thermal stability during the preparation process and is not prone to oxidation and degradation. In the preparation process, a specific second catalyst is added to affect the polymerization process, so that the viscosity of the polymer increases, the polymer has a higher degree of polymerization, and its mechanical properties are improved. During the preparation process, the temperature is increased from a first temperature to a second temperature, and the pressure is reduced from a first pressure to a second pressure. By adjusting the reaction temperature and the reaction pressure, the normal progress of the reaction is ensured, and the processing window is longer than that of the prior art.

[0026] According to the present invention, the rare earth metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium and scandium, preferably at least one of lanthanum, cerium and neodymium.

[0027] According to the present invention, the halogen is selected from at least one of fluorine, chlorine and bromine, preferably chlorine.

[0028] According to the present invention, the alkoxy group is selected from C 3 -C 6 The alkoxy group is preferably a C6 alkoxy group.

[0029] According to the present invention, the aryloxy group is selected from aryloxy groups containing at least one benzene ring or naphthalene ring, and is preferably a phenoxy group.

[0030] According to the present invention, the R 1 Selected from acetylacetonate.

[0031] In the present invention, the inventor unexpectedly discovered during the experiment that when R 1When the acetylacetone group is selected, it can effectively form a coordination structure with the rare earth element, so that the catalyst activity has a higher activity, thereby generating a high viscosity polymer sample.

[0032] According to the present invention, the R 2 An alkyl group selected from C1-C20.

[0033] According to the present invention, the second catalyst is lanthanum acetylacetonate.

[0034] According to the present invention, the molar ratio of the first monomer to the second monomer is 0.1-9:1, preferably 0.2-4:1, and more preferably 0.8-2:1.

[0035] In the present invention, the specific ratio of the first monomer, the second monomer and the third monomer can improve the toughness of the copolymer while maintaining the excellent mechanical properties of the polyglycolic acid itself, such as crystallinity and strength.

[0036] According to the present invention, the molar ratio of the third monomer to the second monomer is 1.1-2:1; preferably 1.15-1.5:1, and more preferably 1.2-1.3:1.

[0037] According to the present invention, the ratio of the molar amount of the first catalyst to the total molar amount of the first monomer and the second monomer is 1:(3.33×10 2 )-10 5 .

[0038] According to the present invention, the ratio of the molar amount of the second catalyst to the total molar amount of the first monomer and the second monomer is 1:(3.33×10 2 )-10 5 .

[0039] In the present invention, there is a synergistic effect between the ratio of the molar amount of the specific catalyst to the specific first catalyst and the total molar amount of the first monomer and the second monomer, and the ratio of the molar amount of the specific second catalyst to the total molar amount of the first monomer and the second monomer, which can significantly increase the viscosity of the polymer, improve the polymer molecular weight and degree of polymerization, reduce the polymer end group content, and help to increase the decomposition temperature of the polymer. At the same time, the increase in the polymer molecular weight is also beneficial to the improvement of the polymerization mechanical properties.

[0040] According to the present invention, the ratio of the molar amount of the first catalyst to the total molar amount of the first monomer and the second monomer is 1:(5×10 2 )-(2×10 4 ), more preferably 1:(2×10 3 )-10 4 .

[0041] According to the present invention, the ratio of the molar amount of the second catalyst to the total molar amount of the first monomer and the second monomer is 1:(2×10 3 )-10 5 , more preferably 1:(2×10 4 )-10 5 .

[0042] According to the present invention, the first catalyst is selected from at least one of phosphoric acid, sulfuric acid, organic sulfonic acid, inorganic metal salt, metal oxide and organic metal salt.

[0043] According to the present invention, the metal element in the inorganic metal salt, the metal oxide and the organic metal salt is selected from at least one of the metal elements in Groups IIB, IIIB, IVB, VB, VIII, IIIA, IV and VA in the periodic table.

[0044] According to the present invention, the metal element in the inorganic metal salt, the metal oxide and the organic metal salt is selected from at least one of the metal elements of Groups IIB, IIIB, IVB, VB, VIII, IIIA, IV and VA in the third, fourth and fifth periods of the periodic table.

[0045] According to the present invention, the metal element in the inorganic metal salt, the metal oxide and the organic metal salt is selected from at least one of zinc, titanium, vanadium, tin, antimony and bismuth.

[0046] According to the present invention, the metal elements in the inorganic metal salt, the metal oxide and the organic metal salt are selected from tin and / or antimony.

[0047] According to the present invention, the metal element in the inorganic metal salt, the metal oxide and the organic metal salt is tin.

[0048] According to the present invention, the metal-binding part in the organic metal salt is selected from C1-C20 oxygen-containing alkanes.

[0049] According to the present invention, the metal-binding part in the organic metal salt is at least one selected from α-alkoxy, α-alkyl monocarboxylic acid, α-alkyl monocarboxylic acid, α,ω-alkyl diacid, alkyl monoketone and polyketone.

[0050] According to the present invention, the first catalyst is selected from at least one of zinc acetate, tetraisopropyl titanate, tetrabutyl titanate, diisopropyl diacetylacetonate titanate, acetylacetonoxy titanate, vanadium oxalate, cobalt oxalate, dibutyl tin oxide, dibutyl tin diacetylacetonate, dibutyl tin diacetate, tin laurate, methylphenyl tin oxide, tetraethyl tin, hexaethyl tin oxide, hexacyclohexyl ditin oxide, didodecyl tin oxide, triethyl hydroxytin, triphenyl hydroxytin, triisobutyl tin acetate, diphenyl tin dilaurate, monobutyl tin trichloride, tributyl tin chloride, dibutyl tin sulfide, butyl hydroxytin oxide, methyl stannic acid, ethyl stannic acid, butyl stannic acid, stannous octoate, stannous acetate, stannous oxalate, antimony trioxide, bismuth neododecanoate, bismuth acetate and bismuth oxalate.

[0051] According to the present invention, the first catalyst is selected from at least one of dibutyltin oxide, dibutyltin diacetylacetonate, dibutyltin diacetate, stannous octoate, stannous acetate, stannous oxalate and antimony trioxide.

[0052] According to the present invention, the first catalyst is selected from at least one of stannous octoate, stannous acetate and stannous oxalate.

[0053] According to the present invention, the first catalyst is stannous oxalate.

[0054] According to the present invention, the dibasic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, phthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-succinic acid, 1,5-pentanedioic acid, 1,6-hexanedioic acid, 1,8-octanedioic acid, 1,10-decanedioic acid and 1,4-cyclohexane dicarboxylic acid.

[0055] According to the present invention, the dibasic acid is at least one selected from 2,5-furandicarboxylic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-succinic acid, 1,6-hexanedicarboxylic acid, 1,10-decanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid.

[0056] According to the present invention, the dibasic acid is at least one selected from 2,5-furandicarboxylic acid, terephthalic acid and 1,10-decanedioic acid.

[0057] According to the present invention, the dibasic acid is terephthalic acid and / or 1,10-decanedioic acid.

[0058] According to the present invention, the dibasic acid anhydride is selected from malonic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, suberic anhydride, sebacic anhydride and phthalic anhydride, preferably sebacic anhydride.

[0059] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, 2-ethyl-2-butyl-1,3-propylene glycol, 1,3-butanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,6-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyethylene glycol, p-phenol, dihydroxyethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4, glycol, isosorbide, isoidol and isomannide.

[0060] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propylene glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, dihydroxyethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4-diol and isosorbide.

[0061] According to the present invention, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, dihydroxyethyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate and isosorbide.

[0062] According to the present invention, the diol is 1,4-butanediol and / or bis(hydroxybutyl) terephthalate.

[0063] According to the present invention, step (1) further comprises: performing a deoxygenation operation before the reaction to ensure that the first esterification reaction and the second esterification reaction are both performed under an inert gas atmosphere.

[0064] In the present invention, deoxygenation is performed in advance to further prevent oxidation during the preparation of polyglycolic acid.

[0065] According to the present invention, the deoxygenation time is 10-100 min, preferably 10-30 min.

[0066] According to the present invention, the first temperature is 100-190°C.

[0067] In the present invention, the specific first temperature ensures the smooth progress of the esterification reaction. The temperature of the esterification reaction cannot be too high or too low. When the temperature of the esterification reaction is lower than 100° C., the esterification reaction rate is too low, which is not conducive to subsequent reactions. When the temperature of the esterification reaction is higher than 190° C., the raw materials are easily sublimated and decomposed, resulting in an excessively high raw material loss rate.

[0068] According to the present invention, the first temperature is 175-185°C.

[0069] According to the present invention, the esterification reaction time is 1-6h.

[0070] In the present invention, the time of the esterification reaction cannot be too long or too short. When the time of the esterification reaction is less than 1 hour, the raw material reaction is not sufficient, the esterification rate is too low, and the raw material loss rate is too high; when the time of the esterification reaction is more than 6 hours, it will cause energy waste.

[0071] According to the present invention, the esterification reaction time is 2-4h.

[0072] According to the present invention, the second temperature is 190-235°C, preferably 200-225°C.

[0073] According to the present invention, the first pressure is 0.1-100 kPa, preferably 0.1-2 kPa.

[0074] According to the present invention, the prepolymerization reaction time is 0.5-2h, preferably 1-2h.

[0075] In the present invention, the pre-polycondensation reaction is first carried out under a low vacuum degree to extract the excess diol, thereby preventing the excessive diol from causing the molecular weight of the polymer to be too low.

[0076] According to the present invention, the second pressure is ≤200Pa, preferably 20-200Pa.

[0077] According to the present invention, the temperature of the polycondensation reaction is 190-235°C, preferably 200-225°C.

[0078] According to the present invention, the polycondensation reaction time is 1-6 hours, preferably 2-4 hours.

[0079] In the present invention, under the conditions of high vacuum and specific polycondensation process, the final polycondensation reaction is carried out until the polymerization reaction is completed, and there will be an obvious system viscosity increase phenomenon, namely, Weissenberg effect.

[0080] The second aspect of the present invention provides a polyglycolic acid copolymer prepared by the above method.

[0081] According to the present invention, the thermal decomposition temperature of the polyglycolic acid copolymer is ≥300° C., and the intrinsic viscosity at 25° C. is ≥1 dL / g.

[0082] In the present invention, the polyglycolic acid copolymer prepared by the specific preparation method has excellent thermal stability and intrinsic viscosity.

[0083] According to the present invention, the thermal decomposition temperature of the polyglycolic acid copolymer is 322° C. and the intrinsic viscosity is 1.2 dL / g.

[0084] The present invention will be described in detail below through examples.

[0085] In the following examples, the glass transition temperature (T g )、Melting point (T m ), crystallization temperature (T c ) parameters were tested by the Q100 differential scanning calorimeter of TA Company in the United States. The instrument is equipped with a mechanical refrigeration device, which can accurately control the heating and cooling process. The instrument temperature is calibrated with n-octane (melting point is -56.76℃) and indium (melting point is 156.78℃). The instrument temperature control is accurate to ±0.01℃, and the detection temperature range is -80℃ to 400℃. The sample dosage is 2-5mg, and all samples are tested in a nitrogen atmosphere with a nitrogen flow rate of 50mL / min and a heating and cooling rate range of 10℃ / min.

[0086] Decomposition temperature (T d ) Tested by Q500 SDT thermogravimetric-differential thermal synchronous measuring instrument of TA Company of the United States, with the temperature of weight loss of 5wt% as the decomposition temperature. Tested in nitrogen atmosphere, nitrogen flow rate is 100mL / min, temperature scanning range is 40-600℃, heating rate is 10℃ / min. Sample dosage is 2-10mg, and placed in platinum crucible for testing.

[0087] The test method of intrinsic viscosity is as follows: accurately weigh 0.1±0.5g of ground polyester sample, dissolve it in chloroform solution containing 5nM, and use 0.5-0.6mm diameter Ubbelohde viscometer in a constant temperature water bath at 25±0.5℃ to measure the outflow time t of pure solvent and polymer solution respectively. 0 and t, the intrinsic viscosity [η] is calculated by the "one-point method" formula [Thomes DK, Thomes TA. J. Appl. Polym. Sci, 1960, 3: 129-131] to obtain:

[0088] [η]=[2(η sp -lnη r )] 1 / 2 / c

[0089] Where: η r =t / t 0 is the relative viscosity; η sp =η r -1 is the specific viscosity, c is the concentration of the polymer solution.

[0090] The mechanical property test method is: using the 5965 universal electronic tensile testing machine of Instron Company of the United States, the unidirectional tensile performance of the sample is tested according to the GB / T1040.2-2006 standard, the tensile rate is 50mm / min, and the test is conducted at room temperature. The sample is a hot-pressed dumbbell-shaped specimen, and each sample is tested 5 times in parallel to obtain the average value.

[0091] Unless otherwise specified, the experimental materials used in the following examples are all commercially available.

[0092] Example 1

[0093] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A1.

[0094] Example 2

[0095] 1.6 mol of glycolic acid, 0.8 mol of terephthalic acid, 1.04 mol of butanediol, 0.6 mmol of stannous oxalate catalyst and 0.06 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess butanediol was extracted and the system temperature did not rise, it was proved that the butanediol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid copolymer butylene terephthalate A2.

[0096] Example 3

[0097] 1.6 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 0.3 mmol of tetrabutyl titanate catalyst and 0.03 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid A3.

[0098] Example 4

[0099] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 0.4 mmol of stannous oxalate catalyst and 0.04 mmol of lanthanum trichloride were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A4.

[0100] Example 5

[0101] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 2 mmol of stannous oxalate catalyst and 0.2 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A5.

[0102] Example 6

[0103] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 3 mmol of stannous oxalate catalyst and 0.03 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A6.

[0104] Example 7

[0105] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 0.3 mmol of stannous oxalate catalyst and 0.3 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A7.

[0106] Example 8

[0107] 2 mol of glycolic acid, 1 mol of sebacic acid, 1.3 mol of ethylene glycol, 10 mmol of stannous oxalate catalyst and 10 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A8.

[0108] Example 9

[0109] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 160° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A9.

[0110] Example 10

[0111] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 8 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid A10.

[0112] Embodiment 11

[0113] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 150 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid A11.

[0114] Example 12

[0115] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 230° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 230° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A12.

[0116] Embodiment 13

[0117] 1.6 mol of glycolic acid ester, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the excess ethylene glycol was extracted and the system temperature did not rise, it was proved that the ethylene glycol had been extracted. The reaction temperature was controlled at 215° C. and the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester A13.

[0118] Comparative Example 1

[0119] The method of Example 1 was followed, except that the comonomers sebacic acid and ethylene glycol were not added.

[0120] 1.6 mol of glycolic acid, 0.16 mmol of stannous oxalate catalyst and 0.016 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. When the temperature at the top of the fractionation tower no longer increased, the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid B1.

[0121] Comparative Example 2

[0122] The method of Example 1 was followed, except that no stannous oxalate was added.

[0123] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol and 0.025 mmol of lanthanum acetylacetonate were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. After the excess ethylene glycol was extracted, the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h, but no polymer was obtained.

[0124] Comparative Example 3

[0125] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol and 0.25 mmol of stannous oxalate catalyst were added into a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 min. The reactor was heated to 185° C. for esterification reaction with a reaction time of 3 h. The reaction temperature was then controlled at 215° C. and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 1 h. After the excess ethylene glycol was extracted, the reaction pressure was controlled at 20 Pa for condensation reaction with a reaction time of 3 h to obtain polyglycolic acid co-polyethylene glycol sebacic acid ester B3.

[0126] Comparative Example 4

[0127] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added to a 500 mL three-necked flask, nitrogen was introduced for deoxygenation for 30 min, the reactor was heated to 185°C, and the esterification reaction was carried out for 3 h; the reaction temperature remained unchanged, the reaction pressure was controlled at 2 kPa, and the prepolymerization reaction was carried out for 1 h; after the excess ethylene glycol was extracted, the reaction pressure was controlled at 20 Pa, and the polycondensation reaction was carried out for 3 h. No polymer was obtained.

[0128] Comparative Example 5

[0129] 1.6 mol of glycolic acid, 0.8 mol of sebacic acid, 1.04 mol of ethylene glycol, 0.25 mmol of stannous oxalate catalyst and 0.025 mmol of lanthanum acetylacetonate were added to a 500 mL three-necked flask, and nitrogen was introduced for deoxygenation for 30 minutes. The reactor was heated to 185°C for esterification reaction with a reaction time of 3 hours. The reaction temperature was then controlled at 215°C and the reaction pressure was controlled at 2 kPa for prepolymerization reaction with a reaction time of 4 hours, but no polymer was obtained.

[0130] Comparative Example 6

[0131] Add 135g glycolic acid, 64g sebacic acid, 28g ethylene glycol, and 0.36g stannous oxalate to a 500mL three-necked flask, and carry out esterification reaction for 6h under stirring, normal pressure, 190℃, reaction temperature, and 100℃ reflux temperature to obtain a precursor. The obtained precursor is placed under stirring, 50kPa reaction pressure, 190℃ reaction temperature, and 60℃ reflux temperature for prepolymerization reaction for 2h to obtain an intermediate. Add 0.14g antioxidant 1010, 0.07g antioxidant 626 to the intermediate, and add 0.36g stannous oxalate, and place under stirring, 20Pa reaction pressure, 200℃ reaction temperature, 65℃ reflux temperature for polycondensation reaction for 6h to obtain a copolymer.

[0132] The performance parameters of Examples 1-13 and Comparative Examples 1-6 were tested, and the results are shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] Test Case

[0137] Mechanical property tests were performed on Examples 1-13 and Comparative Examples 1-6 to obtain Test Examples 1-13 and Comparative Examples 1-6, which were then subjected to performance tests. The test results are shown in Table 2.

[0138] Table 2

[0139]

[0140]

[0141] It can be seen from the results in Table 1 and Table 2 that, compared with Examples 1-3, the types of second monomers added in Examples 1 and 3 are different from those in Example 2. It can be seen that the addition of different monomers makes the finally prepared polymers have different initial properties, and they cannot be compared horizontally with each other. However, from the comparison between Example 2 and Comparative Example 1 (polyglycolic acid homopolymer), it can be seen that the comprehensive performance of the polymer prepared in the present application is better.

[0142] Compared with Comparative Examples 3 and 4, Example 1 shows that no polymer was obtained in Comparative Examples 3 and 4. The technical solution of the present invention can solve the problem that polyglycolic acid is easily oxidized and degraded during the preparation process and is difficult to process.

[0143] Compared with Comparative Examples 1-6, the composite catalyst and the preparation process of the present invention work together to make the polyglycolic acid copolymer prepared according to the technical solution of the present invention have a higher molecular weight and polymer, thereby having higher thermal stability, high viscosity and high toughness;

[0144] Furthermore, compared with Examples 5-8, the ratio of the molar amount of the specific first catalyst to the total molar amount of the first monomer and the second monomer, and the ratio of the molar amount of the second catalyst to the total molar amount of the first monomer and the second monomer act synergistically to enhance the viscosity of the polymer, increase the molecular weight and degree of polymerization of the polymer, and reduce the content of the polymer end groups.

[0145] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a polyglycolic acid copolymer, It is characterized in that The following steps are involved: (1) subjecting a first monomer, a second monomer, and a third monomer to an esterification reaction under the action of a first catalyst and a second catalyst at a first temperature to obtain a precursor; (2) heating the precursor to a second temperature and the first pressure to obtain an intermediate by subjecting the precursor to a prepolymerization reaction; reducing the pressure to a second pressure and subjecting the intermediate to a condensation polymerization reaction to obtain a copolymer; The first monomer is selected from glycolic acid and / or glycolic acid esters; The second monomer is selected from dibasic acids and / or dibasic acid anhydrides; The third monomer is a diol; The second catalyst is RE (R 1 ) 3 Type catalyst, RE is a rare earth metal element, R 1 is selected from halogen, alkoxy, aryloxy, acetylacetonate and R 2 At least one of the COO- groups, R 2 C 1 -C 30 of alkyl.

2. The method according to claim 1, in, The rare earth metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium and scandium, preferably at least one of lanthanum, cerium and neodymium; Preferably, the halogen is selected from at least one of fluorine, chlorine and bromine, preferably chlorine; Preferably, the alkoxy group is selected from C3-C6 alkoxy groups, preferably C6 alkoxy groups; Preferably, the aryloxy group is selected from aryloxy groups containing at least one benzene ring or naphthalene ring, preferably phenoxy; Preferably, the R 1 Selected from acetylacetonate; Preferably, the R 2 An alkyl group selected from C1-C20.

3. The method according to claim 1 or 2, in, The second catalyst is lanthanum acetylacetonate.

4. The method according to any one of claims 1 to 3, in, The molar ratio of the first monomer to the second monomer is 0.1-9:1, preferably 0.2-4:1, more preferably 0.8-2:1; Preferably, the molar ratio of the third monomer to the second monomer is 1.1-2:1; preferably 1.15-1.5:1, more preferably 1.2-1.3:

1.

5. The method according to any one of claims 1 to 4, in, The ratio of the molar amount of the first catalyst to the total molar amount of the first monomer and the second monomer is 1:(3.33×10 2 )-10 5 , preferably 1:(5×10 2 )-(2×10 4 ), more preferably 1:(2×10 3 )-10 4 ; Preferably, the ratio of the molar amount of the second catalyst to the total molar amount of the first monomer and the second monomer is 1:(3.33×10 2 )-10 5 , preferably 1:(2×10 3 )-10 5 , more preferably 1:(2×10 4 )-10 5 .

6. The method according to any one of claims 1 to 5, in, The first catalyst is selected from at least one of phosphoric acid, sulfuric acid, organic sulfonic acid, inorganic metal salt, metal oxide and organic metal salt; Preferably, the metal element in the inorganic metal salt, the metal oxide and the organic metal salt is selected from at least one of the metal elements in Groups IIB, IIIB, IVB, VB, VIII, IIIA, IV and VA in the periodic table; preferably at least one of the metal elements in Groups IIB, IIIB, IVB, VB, VIII, IIIA, IV and VA in the third period, fourth period and fifth period of the periodic table; more preferably at least one of zinc, titanium, vanadium, tin, antimony and bismuth; further preferably tin and / or antimony; further preferably tin; Preferably, the metal-binding part in the organic metal salt is selected from C1-C20 oxygen-containing alkanes; preferably at least one of α-alkoxy, α-alkyl monocarboxylic acid, α-alkyl monocarboxylic acid, α,ω-alkyl diacid, alkyl monoketone and polyketone.

7. The method according to any one of claims 1 to 6, in, The first catalyst is selected from zinc acetate, tetraisopropyl titanate, tetrabutyl titanate, diisopropyl diacetylacetonate titanate, acetylacetonoxy titanate, vanadium oxalate, cobalt oxalate, dibutyltin oxide, dibutyltin diacetylacetonate, dibutyltin diacetate, tin laurate, methylphenyltin oxide, tetraethyltin, hexaethyltin oxide, hexacyclohexyl ditin oxide, didodecyltin oxide, triethylhydroxytin, triphenylhydroxytin, triisobutyltin acetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin The invention relates to a tin oxide selected from the group consisting of tin chloride, dibutyltin sulfide, butyltin hydroxide, methylstannic acid, ethylstannic acid, butylstannic acid, stannous octoate, stannous acetate, stannous oxalate, antimony trioxide, bismuth neododecanoate, bismuth acetate and bismuth oxalate; preferably, the tin oxide is selected from the group consisting of dibutyltin oxide, dibutyltin diacetylacetonate, dibutyltin diacetate, stannous octoate, stannous acetate, stannous oxalate and antimony trioxide; more preferably, the tin oxide is selected from the group consisting of stannous octoate, stannous acetate and stannous oxalate; and further preferably, the stannous oxalate is selected from the group consisting of stannous oxalate.

8. The method according to any one of claims 1 to 7, in, The dibasic acid is selected from at least one of 2,5-furandicarboxylic acid, terephthalic acid, phthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-succinic acid, 1,5-pentanedioic acid, 1,6-hexanedioic acid, 1,8-octanedioic acid, 1,10-decanedioic acid, and 1,4-cyclohexane dicarboxylic acid; preferably at least one of 2,5-furandicarboxylic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-succinic acid, 1,6-hexanedioic acid, 1,10-decanedioic acid, and 1,4-cyclohexane dicarboxylic acid; more preferably at least one of 2,5-furandicarboxylic acid, terephthalic acid, and 1,10-decanedioic acid; further preferably terephthalic acid and / or 1,10-decanedioic acid; Preferably, the dibasic acid anhydride is selected from malonic anhydride, succinic anhydride, glutaric anhydride, adipic anhydride, suberic anhydride, sebacic anhydride and phthalic anhydride, preferably sebacic anhydride; Preferably, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, 2-ethyl-2-butyl-1,3-propylene glycol, 1,3-butanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,6-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyethylene glycol, p-phenol, dihydroxyethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4, glycol, isosorbide, isoidol and isomannide; preferably ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,6-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyethylene glycol, p-phenol, dihydroxyethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, tetrahydrofuran 3,4, glycol, isosorbide, isoidol and isomannide. The present invention is preferably selected from the group consisting of ethylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, 2-ethyl-2-butyl-1,3-propylene glycol, dihydroxyethyl terephthalate, dihydroxypropyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, 3,4-tetrahydrofuran, and isosorbide; more preferably selected from the group consisting of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, dihydroxyethyl terephthalate, dihydroxybutyl terephthalate, dihydroxyhexyl terephthalate, and isosorbide; and further preferably selected from the group consisting of 1,4-butanediol and / or dihydroxybutyl terephthalate.

9. The method according to any one of claims 1 to 8, in, Step (1) also includes: performing a deoxygenation operation before the reaction to ensure that the first esterification reaction and the second esterification reaction are both performed under an inert gas atmosphere; Preferably, the deoxygenation time is 10-100 min, preferably 10-30 min.

10. The method according to any one of claims 1 to 9, in, The first temperature is 100-190°C, preferably 175-185°C; Preferably, the esterification reaction time is 1-6 h; preferably 2-4 h.

11. The method according to any one of claims 1 to 10, in, The second temperature is 190-235°C, preferably 200-225°C; Preferably, the first pressure is 0.1-100 kPa; preferably 0.1-2 kPa; Preferably, the prepolymerization reaction time is 0.5-2h, preferably 1-2h; Preferably, the second pressure is ≤200Pa, preferably 20-200Pa; Preferably, the temperature of the polycondensation reaction is 190-235°C, preferably 200-225°C; Preferably, the polycondensation reaction time is 1-6 h, preferably 2-4 h.

12. The polyglycolic acid copolymer prepared by the method according to any one of claims 1 to 11; Preferably, the thermal decomposition temperature of the polyglycolic acid copolymer is ≥300°C, and the intrinsic viscosity at 25°C is ≥1dL / g.

Citation Information

Patent Citations

  • Degradable copolyester composition, anti-static biodegradable film material, film and application

    CN115637026A

  • High-molecular-weight aliphatic copolyester and its production

    JP1996311181A

  • Biodegradable high molecular weight aliphatic polyesterether and its production

    JP1999166044A

  • Process for making poly(glycolic acid) for containers and films with reduced gas permeability

    US20210198424A1